Strategi Pengembangan Daya Tarik Wisata Science Center sebagai Wisata Edukasi di Kabupaten Bandung - First Son Joseph; Emron Edison; Titing Kartika (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
The purpose of this research is to determine the tourism attraction and development strategy in the science center of Bandung Regency. This research was conducted using a qualitative descriptive approach and SWOT analysis. Data collection was carried out through observation, interviews, and documentation. The results of the study showed that the tourism attractions in the science center were quite diverse, ranging from photo spots to interactive exhibits. However, additional tourism attractions need to be added to attract more tourists. Regarding the development strategy of tourism attractions in the science center, it is necessary to observe the environment (internal and external factors) and develop strategies through the SWOT matrix to produce alternative strategies translated into short-term goals, such as: Intensive promotion, Collaborating with other institutions, Promoting the existing educational and cultural attractions, Adding new attractions, Preparing or training tour guides who understand the exhibits, Adding several new spots of attraction, Considering natural factors for tourists' safety, Providing professional guides, medium-term goals such as providing various souvenirs, and long-term goals.